“We have botched them and patched them”: Modernity and Restoration in Henry James’s Italian Hours - Monica MANOLESCU-OANCEA (E-REA)
This article focuses on Henry James’s Italian Hours from the perspective of the author’s response to the restoration of Italian architecture and more generally to the place of modernity in the Italian cityscape. A central issue in the intellectual and artistic debates of the 19th century, the process of restoration triggered various responses. Henry James, just like John Ruskin, was horrified by the results of restoration in Italy, for reasons having to do with his vision of the organic growth of buildings, with his stance as a discreet and “uninvestigating” traveller and with his criticism of “improvement” as bad taste. Although he rejects renovation as interference of the present in the past, he accepts, albeit reluctantly, the necessity of “young Italy” to become a modern state. James’s nuanced response to Ruskin is part of his ambivalent attitude as regards the evolution of Italian cities towards modernity.